Development of dermally absorbed copper(ii) complexes as potential anti-inflammatory drugs - Vicatos, Giselle Marianthi (Department of Chemistry, 2022)
Rheumatoid arthritis (RA) is a debilitating disease affecting 5% of the world's population and there is no cure. Copper(II) complexes have been reported to have anti-inflammatory activity and alleviate the symptoms associated with the disease. The present study focuses on the design of new drugs that could be used to change the bioavailability of copper(II) and hence alleviate the inflammation. The tripeptides, glycyl-L-leucyl-L-histidine (GLH), sarcosyl-L-leucyl-Lhistidine (Sar-LH), glycyl-L-phenylalanyl-L-histidine (GFH) and sarcosyl-L-phenylalanyl-Lhistidine (Sar-FH) were designed to resemble the natural in vivo copper(II) transporter, human serum albumin, so that they could be selective for copper(II). The preferred route of administration is dermal absorption and so sarcosine was added to improve the lipophilicity of the drug. This administration method was chosen since it is both nonharmful and convenient for patients. The stability of the complexes was measured using glass electrode potentiometry and their solution structure studied using UV-Vis spectrophotometry, CW-EPR spectroscopy, 1H NMR, ESI-MS and molecular modelling calculations. The presence of sarcosine did not significantly affect the stability of the complexes. Several species were found to exist in solution depending on the pH, but at pH 7, the CuLH-2 species predominated for all four tripeptides. In this species, the ligand was found to coordinate to copper(II) via the terminal amine-N, the two amide-Ns and imidazole-N, in a square planar geometry. Using a computer model of blood plasma, all four ligands were found to mobilise copper(II), without disrupting the homeostasis of nickel(II), zinc(II) or calcium(II) in the order of GFH > Sar-FH > GLH > Sar-LH. GFH increased the low molecular mass copper(II) species by 40.7 times at 0.1 mM. The lipophilicity of the complexes was estimated by measuring their octanol/water partition coefficients. All the complexes were found to be hydrophilic with log Poct/aq ranging from -3 to -2. Dermal absorption was estimated using an artificial membrane and a Franz cell. Only a moderate increase in membrane permeability of copper(II) was found. The stability of the copper(II) complexes, their ability to mobilise copper(II) from endogenous sources and their improved dermal absorption, justifies further testing of this class of ligand as potential, dermally absorbable, anti-inflammatory drugs.